Preparation and application of tannin coupled cottonseed protein composite material for uranium removal
By mixing cottonseed protein with distilled water under a nitrogen atmosphere, adding hydrogen peroxide solution and ascorbic acid, and then adding plant tannins to prepare a tannin-coupled cottonseed protein composite material (CPI-BT) for uranium removal, it solves the problems of high cost, poor effect and secondary pollution in the prior art, and achieves rapid and effective uranium removal, and has environmentally friendly characteristics.
Patent Information
- Application Number
- CN202411769839.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The prior art has problems such as high cost, poor effect and possible secondary pollution in uranium removal, and the surfactants used in traditional ion flotation have environmental risks and non-biodegradable problems.
Tannin-coupled cottonseed protein composite (CPI-BT) was prepared by mixing cottonseed protein with distilled water under a nitrogen atmosphere, adding hydrogen peroxide solution and ascorbic acid, followed by adding plant tannins, and after stirring reaction, dialysis and freeze-drying, a tannin-coupled cottonseed protein composite (CPI-BT) was prepared for uranium removal.
It realizes rapid and effective separation of uranyl in the water environment and on different solid surfaces, and has the characteristics of simple preparation method, easy biodegradation, and environmentally friendly, and has good application prospects in uranium removal.
Smart Images

Figure CN119588320A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of radioactive element processing, and more specifically, relates to the preparation and application of a tannin-coupled cottonseed protein composite material for uranium removal. Background Art
[0002] Tannin is a low-cost, renewable natural chemical with a wide range of sources and a unique structure. It can react with alkaloids, polysaccharides, proteins, metal ions and other chemicals and can be used for metal adsorption, food coloring, antioxidants, leather tanning agents, etc. Tannin can scavenge free radicals and chelate metal ions involved in oxidation reactions, which is attributed to the presence of multiple phenolic hydroxyl groups in tannin molecules. These groups can donate hydrogen atoms or electrons to neutralize reactive oxygen and prevent oxidative damage. Bayberry tannin (BT) is a condensed tannin, and previous studies have shown that it has antioxidant and antimicrobial properties.
[0003] Nuclear energy is regarded as an important candidate energy source to meet future energy needs due to its high efficiency and clean characteristics. Uranium is currently the most basic nuclear fuel, and its stable supply means the long-term development of nuclear energy. However, due to improper disposal of radionuclide wastewater from large nuclear power plants, unpredictable nuclear accidents, nuclear waste reprocessing, oil and gas leaks, land uranium mining, military operations and other accidents, radioactive uranium is discharged into the environment, posing a serious threat to human health and ecological security. During the operation and decommissioning of nuclear power plants, contact with radioactively contaminated surfaces of machines and components poses a major risk to the health and safety of workers, clothing and the environment. Therefore, effective and timely research on surface radioactive decontamination is as important as environmental remediation.
[0004] At present, chemical precipitation, oxidation and adsorption are conventional technologies for removing metal ions from water environments. However, these technologies have disadvantages such as high cost, poor effect and possible secondary pollution. Compared with traditional methods for treating water environments contaminated by metal ions, ion flotation has several important advantages, such as shorter treatment time, minimal space requirements, low energy consumption and ion selectivity. Foam purification can effectively prevent surface corrosion, significantly reduce waste generation, and can be used to purify solid surfaces with complex shapes. Surfactants used in ion flotation have environmental risks, unstable chemical properties, bioaccumulation, high cost and non-biodegradability. Therefore, in the commercial application of ion flotation, environmentally friendly and efficient materials that can both chelate and foam are urgently needed. The synergistic effect between the large number of phenolic hydroxyl groups in tannin molecules is the reason for its significant complexing ability with metal ions. However, its high solubility makes it difficult to use in water environments and usually requires modification to be effective. Summary of the invention
[0005] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0006] In order to achieve these objects and other advantages of the present invention, a method for preparing a tannin-coupled cottonseed protein composite material for uranium removal is provided, comprising the following steps:
[0007] Step 1: Add cottonseed protein to distilled water under a nitrogen atmosphere, stir, then add hydrogen peroxide solution and ascorbic acid, continue stirring to obtain a cottonseed protein mixed solution;
[0008] Step 2: adding plant tannin to the cottonseed protein mixture to make the concentration of plant tannin in the mixture be 0.3-1.1 mmol / L, stirring for reaction, dialyzing to remove unreacted plant tannin, and freeze-drying to obtain a tannin-coupled cottonseed protein composite material, namely CPI-BT.
[0009] Preferably, in step 1, the mass volume ratio of cottonseed protein to distilled water is 1 g:50-150 mL.
[0010] Preferably, in step 1, the stirring temperature is 20 to 30° C. and the stirring time is 1 to 3 hours.
[0011] Preferably, in step 1, the concentration of the hydrogen peroxide solution is 0.5 to 1.5 mol / L.
[0012] Preferably, in step 1, the mass volume ratio of cottonseed protein to hydrogen peroxide solution is 1 g:1-5 mL; the mass volume ratio of cottonseed protein to ascorbic acid is 1:0.2-0.7.
[0013] Preferably, in step 2, the plant tannin is one or more of bayberry tannin, persimmon tannin, apple tannin, tea tannin and grape tannin.
[0014] Preferably, in step 2, the stirring reaction temperature is 20 to 30°C for 20 to 30 hours; freeze drying is freeze drying at -100 to -50°C for 40 to 60 hours.
[0015] Preferably, the method further comprises modifying the prepared tannin-coupled cottonseed protein composite material:
[0016] S1. Add the prepared tannin-coupled cottonseed protein composite material to a 50-80 wt % ethanol solution, then add ferrous chloride and polyethylene glycol-400, adjust the pH to 2-3, and stir at 20-30° C. and 100-200 rpm for 2-4 h to obtain a mixed solution A;
[0017] S2. Add tetrabutyl titanate and citric acid to the mixed solution A, adjust the pH to 3-5, and stir at 40-50° C. and 100-200 rpm for 2-4 hours to obtain a mixed solution B;
[0018] S3. Add 50-200 mL of 0.1-0.5 mol / L sodium borohydride solution to the mixed solution B, stir at 20-30° C. and 100-200 rpm for 1-3 h, collect the precipitate by centrifugation, wash it, and freeze-dry it to obtain a modified tannin-coupled cottonseed protein composite material.
[0019] Preferably, in S1, the mass volume ratio of the tannin-coupled cottonseed protein composite material, the ethanol solution, ferrous chloride and polyethylene glycol-400 is 1 g: 100-300 mL: 0.05-0.2 g: 0.05-0.2 g.
[0020] Preferably, in S2, the mass ratio of tetrabutyl titanate, citric acid and the tannin-coupled cottonseed protein composite material in step 1 is 0.1-0.5:0.05-0.2:1.
[0021] Application of a tannin-coupled cottonseed protein composite material prepared by the preparation method described above in uranium removal in water environments.
[0022] Application of the tannin-coupled cottonseed protein composite material prepared by the preparation method described above in removing uranium from textile materials.
[0023] The invention discloses an application of a tannin-coupled cottonseed protein composite material prepared by the preparation method described above in the removal of uranium from glass, metal and ceramic surfaces.
[0024] The present invention includes at least the following beneficial effects: the present invention prepares a tannin-coupled cottonseed protein composite material through a free radical-mediated covalent action between tannin and cottonseed protein (CPI), utilizes the abundant ortho-phenolic hydroxyl groups in the tannin structure and the amino groups, carboxyl groups and the like of cottonseed protein to coordinate with uranyl ions, thereby realizing a rapid and effective separation of uranyl in an aqueous environment and on different solid surfaces. The tannin-coupled cottonseed protein composite material of the present invention has the characteristics of simple preparation method, easy biodegradability, and environmental friendliness, and has good application prospects in the safe and efficient treatment of radionuclide pollution in aqueous environments and on solid surfaces; in addition, the CPI-BT prepared by the present invention is a promising substitute for chemical surfactants in the food, pharmaceutical and non-food industries, and provides new insights into the application of antioxidant emulsifiers as a safe and low-cost emulsifier in the repair of radionuclide-contaminated aqueous environments or solid surfaces.
[0025] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1The polyphenol content (A), binding rate and substitution degree (B) of the tannin-coupled cottonseed protein composite materials prepared in Examples 1 to 3;
[0027] Figure 2 FTIR images of the tannin-coupled cottonseed protein composite material and CPI prepared in Examples 1 to 3;
[0028] Figure 3 The CD spectra of the tannin-coupled cottonseed protein composite material and CPI prepared in Example 3;
[0029] Figure 4 The XPS graph of the tannin-coupled cottonseed protein composite material and CPI prepared in Example 3;
[0030] Figure 5 The SEM images of the tannin-coupled cottonseed protein composite material and CPI prepared in Example 3;
[0031] Figure 6 The contact angle images of the tannin-coupled cottonseed protein composite material and the CPI solution prepared in Example 3 on the paraffin surface;
[0032] Figure 7 The surface tension diagram of the tannin-coupled cottonseed protein composite material and CPI prepared in Example 3;
[0033] Figure 8 The foaming ability and foam stability of the tannin-coupled cottonseed protein composite material and CPI prepared in Example 3;
[0034] Fig. 9 The EAI (A) and ESI (B) comparison diagram of the tannin-coupled cottonseed protein composite material and CPI prepared in Example 3;
[0035] Fig.10 This is a comparison chart of the DPPH free radical scavenging activity of the tannin-coupled cottonseed protein composite material prepared in Example 3 and CPI and BT at different concentrations;
[0036] Fig.11 This is a comparison chart of the ABTS free radical scavenging activity of the tannin-coupled cottonseed protein composite material prepared in Example 3 and CPI and BT at different concentrations;
[0037] Fig.12 A is the adsorption capacity of the tannin-coupled cottonseed protein composite material prepared in Example 3 at different pH values; Fig.12 B is the adsorption capacity and uranium removal rate of the tannin-coupled cottonseed protein composite material prepared in Example 3 at different dosages;
[0038] Fig.13 The adsorption capacity of the tannin-coupled cottonseed protein composite material prepared in Example 3 under different ventilation volumes;
[0039] Fig.14 The adsorption capacity change over time of the tannin-coupled cottonseed protein composite material prepared in Example 3 (A) and the kinetic fitting curve of the removal process (B);
[0040] Fig.15 The uranium adsorption capacity of the tannin-coupled cottonseed protein composite material prepared in Example 3 in a coexisting ion system;
[0041] Fig.16 The tannin-coupled cottonseed protein composite material prepared in Example 3 was prepared at different UO2 2+ Adsorption capacity at initial concentration (A), linear fitting of Langmuir model (B), linear fitting of Freundlich model (C), and linear fitting of Temkin model (D);
[0042] Fig.17 A is UO2 2+ SEM images and elemental composition of CPI-BT-U after adsorption; Fig.17 B is the FTIR graph of CPI-BT and CPI-BT-U; Fig.17 C is the EDS mapping image of CPI-BT-U;
[0043] Fig.18 A is the XPS spectra of CPI-BT and CPI-BT-U; Fig.18 B is the U4f high-resolution spectrum of CPI-BT-U; Fig.18 C is the N1s high-resolution spectrum of CPI-BT-U; Fig.18 D is the O1s high-resolution spectrum of CPI-BT-U;
[0044] Fig.19 The stain removal rates of the tannin-coupled cottonseed protein composite material prepared in Example 3 on cotton fabric (A), ceramic (B), glass (C), and metal (D). DETAILED DESCRIPTION
[0045] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0046] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0047] Example 1
[0048] A method for preparing a tannin-coupled cottonseed protein composite material for uranium removal, comprising:
[0049] Step 1: Under a nitrogen atmosphere, add 1 g of cottonseed protein to 100 mL of distilled water, stir for 2 h, then add 2 mL of 1.0 M hydrogen peroxide solution and 0.5 g of ascorbic acid, stir at 25 ° C for 2 h to obtain a cottonseed protein mixture;
[0050] Step 2: Add bayberry tannin to the cottonseed protein mixture to make the concentration of bayberry tannin in the mixture 0.35 mM, stir and react at 25°C for 24 hours, dialyze to remove unreacted bayberry tannin, and freeze-dry at -80°C for 48 hours to obtain a tannin-coupled cottonseed protein composite material, namely CPI-BT 0.35.
[0051] Example 2
[0052] In this example, the concentration of bayberry tannin is 0.70 mM, and the remaining steps are the same as those in Example 1 to prepare CPI-BT 0.70.
[0053] Example 3
[0054] In this example, the concentration of bayberry tannin is 1.05 mM, and the remaining steps are the same as those in Example 1 to prepare CPI-BT 1.05.
[0055] The total phenol content, binding rate and substitution degree were determined using the Folin-Ciocalteu reagent method: 1 mL of 1 mg / mL sample solution, 3 mL of distilled water, 1 mL of Folin-Ciocalteu reagent (1 M) and 3 mL of Na2CO3 (7.5 wt%) were mixed evenly in a 10 mL centrifuge tube. The resulting mixture was incubated in the dark at room temperature for 1 hour. The absorbance of the mixture was measured at 765 nm using a UV-visible spectrophotometer (UV-5500PC, Metash, Shanghai, China). Gallic acid standards with a concentration range of 0.05 to 0.25 mg / mL were used to prepare a standard curve, and water was used as a blank. The BT equivalent content in CPI-BT was expressed as mg BT equivalent per gram of CPI-BT (mg BTE / g). The binding rate and substitution degree were calculated as follows:
[0056]
[0057] The polyphenol content, binding rate and degree of substitution of the tannin-coupled cottonseed protein composite materials prepared in Examples 1 to 3 are as follows: Figure 1 shown. Figure 1 A shows that the content of polyphenols bound to proteins in CPI-BT increased significantly with the increase of BT concentration (0.35-1.05 mM). At 1.05 mM BT, the maximum value observed was 108.88 BTE mg / g. This may be because there are more opportunities for nucleophilic addition events to occur at high BT concentrations, thereby increasing the degree of cross-linking. Figure 1B shows the binding rate between CPI and BT, which increases significantly from 0.35 to 0.70 mM but remains almost unchanged after further increase in BT concentration; however, the degree of substitution increases significantly with increasing BT concentration. These analyses confirm the strong binding of BT to CPI and the successful synthesis of CPI-BT.
[0058] FTIR is used to characterize the secondary structure changes of proteins after forming conjugates with BT. Figure 2 The FTIR images of the tannin-coupled cottonseed protein composite material and CPI prepared in Examples 1 to 3 are shown in Figure 1. It can be seen that the four different important peaks correspond to four different amide bonds, namely, amide A (-3372.74 cm -1 )、Amide I(~1652.21cm -1 )、Amide II (~1545.61cm -1 ) and amide III (~1396.98 cm -1 ). Compared with CPI, these bands in CPI-BT changed in both peak position and shape, indicating that the secondary structure of CPI in the conjugate was changed. After CPI binding, the amide peak intensity increased and became more obvious with increasing BT concentration. Due to CPI-BT binding, the peak position of amide I was changed from 1652.21 cm in CPI to -1 Slightly moved to 1647.62cm -1 ; Compared with CPI, the intensity of the amide II peak in the CPI-BT spectrum is significantly higher, indicating more CN stretching accompanied by NH bending mode. The increase in intensity may be due to the increase in the number of amide bonds caused by the binding of phenolic compounds to proteins.
[0059] Figure 3 CD spectra of the tannin-coupled cottonseed protein composite material and CPI prepared in Example 3. It can be seen that there are obvious differences between the spectral trends of CPI and CPI-BT. The molar ellipticity of CPI and CPI-BT has decreased significantly, and the peak has blue-shifted from 197.02nm to 192.84nm. There is also a significant negative attenuation in the peak at 225nm, indicating the loss of α-helix in CPI, which indicates that a certain degree of unfolding has occurred in the protein structure. These changes indicate that the overall structure is not maintained, and the coupling process has changed the conformation of CPI and the structural content between the secondary structures of the protein.
[0060] XPS was used to analyze the effect of BT grafting on the chemical composition distribution of CPI. Figure 4As shown in Figure 2, the surface of CPI is mainly composed of C, N and O. After the coupling process, the XPS graph of CPI-BT showed no obvious new bands, which was comparable to that of native CPI, and the characteristic peak at 400 eV related to C=N and CN showed a higher intensity. This result further confirmed that BT was successfully bonded to the CPI backbone.
[0061] Figure 5 The SEM images of the tannin-coupled cottonseed protein composite material and CPI prepared in Example 3. It can be seen that the particles of CPI are dense, with a relatively smooth and compact structure, while the particles of CPI-BT are relatively loose, with increased surface roughness and small pores. BT is a highly hydrophilic molecule, so their grafting onto proteins changes the molecular structure, as shown by FTIR and CD analysis and the hydrophilic / hydrophobic ratio of CPI, and these changes create favorable conditions for its interaction with water molecules.
[0062] The assessment of surface hydrophobicity can usually be achieved through contact angle analysis. Figure 6 The contact angle values and images of the tannin-coupled cottonseed protein composite material and CPI solution prepared in Example 3 on the paraffin surface. It can be seen that the contact angle between water and the surface of the paraffin block is 134.0°, indicating that the paraffin is hardly wetted. However, after the addition of CPI, the contact angle value between water and paraffin decreased, and became more obvious when CPI-BT was added, with the contact angle decreasing from 134.0° for water to 101.2° for CPI, and further to 92.5° for CPI-BT. This shows that CPI-BT exhibits good hydrophilicity, which may be due to the increase in carboxyl content during the deamidation reaction.
[0063] Figure 7 The surface tension diagram of the tannin-coupled cottonseed protein composite material and CPI prepared in Example 3, CPI and CPI-BT solutions with a concentration range of 0.1 to 1 mg / mL were prepared using distilled water, and the surface tension of CPI and CPI-BT was analyzed using a tensiometer K100 (Kruss, Germany) and the Du Noüy ring method. It can be seen that within the first 50 seconds, the surface tension dropped rapidly, then slowly and steadily dropped, and tended to stabilize. Protein molecules in aqueous solution are usually folded into a coil shape to hide the hydrophobic region in the center of the coil and expose the hydrophilic group to the water. On the other hand, when the protein molecule approaches the air-water interface, it partially unfolds and aligns its hydrophobic group with the air phase. At all concentrations, CPI-BT reduced the surface tension between the solution and the air phase, and the effect was better than CPI; the higher the protein concentration, the greater the reduction in surface tension, which means that CPI-BT has a better ability to reduce surface tension than CPI, which may be due to partial unfolding during the binding process.
[0064] Both the structural and functional properties of proteins are affected by the binding of proteins to polyphenols. Therefore, the way in which proteins and polyphenols interact can enhance the latter's ability to resist oxidation and form foams or emulsions. Changes in the secondary and tertiary structures of CPIs can affect their surface charge density and spatial conformation, ultimately affecting their functionality. Figure 8 The foaming ability and foam stability of the tannin-coupled cottonseed protein composite material and CPI prepared in Example 3. It can be seen that after CPI is coupled with BT, the foaming ability and foam stability are significantly increased. Generally speaking, the ability of an emulsifier to reduce the surface tension of water is the reason for its foaming property. The more the emulsifier can reduce the surface tension of water, the more foam it produces, and vice versa. After standing for 30 minutes, the foam of both samples decreased. The large interface between the gas phase and the liquid phase, coupled with the strong thermodynamic instability, can cause leakage, weakening, gas diffusion and bubble defoaming of the liquid film layer. The foaming ability of CPI-BT (52.8%) is significantly higher than that of CPI (13.3%). Therefore, covalent coupling significantly improves the stability of the protein film.
[0065] Emulsifying ability is a characterization of the adsorption capacity of proteins at the oil-water interface. Emulsifying ability indicates the stable interfacial area per unit weight of protein. The emulsifying ability of proteins is usually evaluated by EAI and ESI. The higher the EAI and ESI values, the stronger the emulsifying ability. Fig. 9 A and 9B are the EAI and ESI comparison diagrams of the tannin-coupled cottonseed protein composite material and CPI prepared in Example 3, respectively. It can be seen that the EAI and ESI of CPI-BT are higher than those of CPI. The concentration of protein also greatly affects the EAI. When the concentration of all samples increases from 5 mg / mL to 10 mg / mL, the EAI values decrease. However, the EAI of CPI-BT is 27.24% higher than that of CPI. In addition, the ESI value of CPI-BT increases, which means that the stability of the emulsion is better than that of CPI. This can be attributed to the increase in hydrophilicity and the increase in exposed hydrophobic sites, which promotes the interaction between the protein and the interface of nearby oil droplets.
[0066] Antioxidant activity test
[0067] (1) ABTS free radical scavenging test
[0068] A solution of ABTS (7.0 mM) containing potassium persulfate (2.5 mM) was prepared and stored in the dark for 16 h, and diluted with water to obtain a working solution with an absorbance of 0.70 ± 0.04 at 734 nm; the sample solution (1 mL, 0.5, 1 mg / mL) was added to 4 mL of the working solution, shaken evenly, and the mixture was reacted at room temperature in the dark for 20 min, and the absorbance was measured at 734 nm using a spectrophotometer, and the ABTS free radical scavenging rate was calculated using the following formula:
[0069] ABTS free radical scavenging rate (%) = (Ac-As) / Ac×100%
[0070] Where As is the absorbance of the working solution after adding the sample solution, and Ac is the absorbance of the negative control prepared with phosphate buffer (100 mM, pH 7.0);
[0071] (2) DPPH free radical scavenging test
[0072] The sample solution (2 mL, 0.5, 1 mg / mL) was mixed with 3 mL of DPPH solution (0.004% methanol solution), reacted at room temperature in the dark for 30 min, and the absorbance was measured at 517 nm using a spectrophotometer. The DPPH free radical scavenging rate was calculated using the following formula:
[0073] DPPH free radical scavenging rate (%) = (Ac-As) / Ac×100%
[0074] Wherein, As is the absorbance of the DPPH solution after adding the sample solution, and Ac is the absorbance of the negative control prepared with phosphate buffer (100 mM, pH 7.0).
[0075] Cottonseed protein is a good source of bioactive peptides with good antioxidant activity, however, they have limitations such as poor solubility and stability in aqueous environments. BT has high antioxidant activity and solubility. The interaction between CPI and BT in the composite material may produce a synergistic effect, with greater antioxidant activity and improved performance of their combination. DPPH radical is a stable free radical that can capture a hydrogen atom from antioxidants and form a stable DPPH-H molecule, therefore, DPPH test is often used to evaluate the primary antioxidant capacity of compounds. Fig.10 The DPPH radical scavenging activity comparison diagram of the tannin-coupled cottonseed protein composite material prepared in Example 3 and CPI and BT at different concentrations (0.5 mg / mL and 1 mg / mL) shows that BT exhibits excellent DPPH scavenging activity (>85%) at all tested concentrations, while the scavenging activity of CPI is less than 21.3%, and the scavenging activity of CPI-BT is significantly higher than that of CPI. In the scavenging reaction of this test, the degree of reaction depends on the hydrogen supply capacity of the antioxidant. Since BT is known to be a rich source of adjacent phenolic hydroxyl groups and has significant metal binding capacity, the improvement in the scavenging activity of CPI-BT can be attributed to the free hydroxyl groups from BT introduced into CPI after binding. These results show that the introduction of BT into CPI can provide a strong DPPH radical scavenging activity for the resulting composite material.
[0076] Fig.11The ABTS free radical scavenging activity comparison chart of the tannin-coupled cottonseed protein composite material prepared in Example 3 and CPI and BT at different concentrations (0.5 mg / mL and 1 mg / mL). It can be seen that BT exhibits excellent ABTS scavenging activity (>90%) at all tested concentrations, while the scavenging activity of CPI is less than 59%, and the scavenging activity of CPI-BT is 28% higher than that of CPI. It is reported that peptides with more hydrophilic groups react easily with ABTS. Therefore, since the hydrophilicity of CPI increases after the hydrophilic BT is bound to CPI, this may help to improve the scavenging activity of CPI-BT. These results show that when BT is introduced into CPI, the resulting composite material has a significant ABTS free radical scavenging effect.
[0077] Uranium removal test in water environment (ion flotation method): The foaming device consists of a column 300 mm high and 30 mm in diameter; a porous sintered material that can form tiny bubbles with a diameter of about 2 mm; a uranyl nitrate solution is prepared, in which UO2 2+ The concentration is 20 mg / L, and the pH is adjusted to 6 using 0.1 M sodium hydroxide and 0.1 M HNO3. 100 mL of uranyl nitrate solution and 20 mg of sample are added to a conical flask, weighed and thoroughly mixed. Then, the mixture is transferred to a foaming device and an air pump is used to generate foam in the column. The ventilation rate is 2.0 L / min. During this process, the emulsifier bubbles quickly condense with the UO2 in the solution. 2+ The complex was formed, and the reaction time was 30 min at a temperature of 25 °C. Each sample was collected about 5 cm above the porous sinter, and the outlet foam was collected into a conical flask using an outlet tube. Arsenazo III was used as a complexing agent and a colorimetric agent, and a UV-visible spectrophotometer (UV-5500PC, Metash, Shanghai, China) was used to detect UO2 2+ Concentration, each test was repeated three times or more, and the average value was taken for analysis. Adsorption capacity Q e The uranium removal efficiency RE is expressed by the following formula:
[0078]
[0079] In the formula, C0 and C e Represents UO2 before and after removal 2+ concentration (mg / L), V is the volume of the solution used (L), Q e is the adsorption capacity (mg / g), W is the mass of the sample (g), and RE is the uranium removal efficiency (%).
[0080] The equilibrium time data were removed by fitting the pseudo-first-order and pseudo-second-order adsorption equations, and the nonlinear expression of pseudo-first-order adsorption was calculated as follows:
[0081]
[0082] The nonlinear expression for pseudo-secondary adsorption is calculated as follows:
[0083]
[0084] In the formula, t represents the reaction time (min), q e and q t represent the adsorption capacity at equilibrium and at any time (mg / g), K1 is the pseudo-first-order adsorption rate constant (g mg -1 min -1 ), K2 is the pseudo-secondary adsorption rate constant (g mg -1 min -1 );
[0085] Initial concentration of UO2 2+ The removal rate influence data are fitted using the Langmuir and Freundlich models. The expressions of the Langmuir and Freundlich models are as follows:
[0086]
[0087] In the formula, q e Indicates UO2 2+ Equilibrium adsorption capacity (mg / g), q max represents the saturated adsorption capacity (mg / g) in the Langmuir model, C0 and C e UO2 at the beginning and after the reaction 2+ Concentration (mg / L), K L is the Langmuir model constant, determined by the exchange equilibrium constant (L / mg), K F is the Freundlich constant (mg / g)(L / mg) 1 / n , 1 / n represents the coefficient of adsorption site heterogeneity.
[0088] Fig.12 A is the adsorption capacity of the tannin-coupled cottonseed protein composite material prepared in Example 3 at different pH values (4.0-9.0); Fig.12 B is the adsorption capacity and uranium removal rate of the tannin-coupled cottonseed protein composite material prepared in Example 3 at different dosages (10-50 mg). Generally speaking, the initial pH value of the solution has a significant effect on the removal of metal ions. This experiment investigated the effect of pH value on the uranium removal capacity of CPI-BT. Fig.12A illustrates how pH (4.0-9.0) affects the uranium removal capacity of CPI-BT. The adsorption capacity increases with increasing pH, reaches a maximum at pH 6, and then decreases with further increases in pH. The pH value may have an effect on the functional groups of the emulsifier, the ionic balance of the medium, and the surface charge. The results show that the adsorption performance first increases and then decreases. In the pH range of 4.0 to 6.0, the adsorption capacity increases significantly from 60.48 mg / g to 99.08 mg / g, and then decreases to 74.36 mg / g at pH 9.0. The main reason for this may be the H generated at lower pH values. + The number is large, which makes the adsorption sites such as phenolic hydroxyl groups easily protonated and leads to electrostatic repulsion between the protonated adsorbent and the positively charged adsorbent; at higher pH values, these groups can also be deprotonated, which can reduce the binding sites available for adsorption. In addition, at higher pH values, foam is formed rapidly and therefore cannot fully contact with uranium, resulting in lower removal capacity. This shows that CPI-BT is suitable for uranium adsorption under weakly acidic and neutral conditions. Therefore, pH 6 was selected for all subsequent tests. Fig.12 As shown in B, as the amount of CPI-BT increases from 10 mg to 50 mg, the adsorption capacity gradually decreases, but the removal rate increases sharply. When the amount is 50 mg, the removal rate of CPI-BT is 97.2%, which is a high removal efficiency. This can be attributed to the increase in the surface area of CPI-BT, more available binding sites, and the UO2 2+ The supply of is limited, and the excess reaction sites are still unsaturated. In view of the high adsorption capacity and removal rate of CPI-BT, 20 mg was selected as the optimal adsorbent dosage.
[0089] Fig.13 The adsorption capacity of the tannin-coupled cottonseed protein composite material prepared in Example 3 at different ventilation rates. It can be seen that when the ventilation rate is in the range of 0 to 2.0 L / min, the foam is formed more slowly and is more difficult to be completely removed from the surface at a lower flow rate. The increase in ventilation rate increases the removal capacity with the increase in gas flow rate, but this improvement is not obvious. The reason for this phenomenon may be that higher ventilation rate increases the amount of bubble rupture and causes the separation of ions adhering to the foam.
[0090] Fig.14 A is the change of adsorption capacity of the tannin-coupled cottonseed protein composite material prepared in Example 3 over time. It can be seen that as time goes by, UO2 2+ was removed rapidly, reaching a peak value in less than 30 minutes. Therefore, the adsorption equilibrium time was 30 minutes, indicating that the UO2 2+Can be completely removed. Due to the sufficient number of active chelation sites on CPI-BT, the removal process proceeds quickly. In the initial removal stage, sufficient binding sites of CPI-BT can be quickly chelated. As the adsorption process proceeds, the available binding sites become fewer and fewer, thus slowing down the removal speed.
[0091] The obtained kinetic data were fitted using pseudo-first-order and pseudo-second-order kinetic models to understand the adsorption mechanism. The fitting curve results are shown in Fig.14 B and Table 1. It can be seen that UO2 2+ More than 90% of the adsorption equilibrium occurred within the first 10 minutes, and then slowly increased over the next 90 minutes. The pseudo-second-order linear model can more accurately describe the elimination process. The UO2 calculated by the pseudo-second-order model 2+ Adsorption capacity (q e-cal , 97.734 mg / g) and the actual result (q e-exp , 99.077mg / g). This result shows that chemical reaction plays a leading role in the removal process.
[0092] Table 1
[0093]
[0094] Since other metal ions are often present in radioactively contaminated areas, one of the challenges in the practical application of decontamination agents is the degradation of UO2 2+ In order to examine the effect of other ions on the removal performance of CPI-BT, the removal of UO2 by CPI-BT was studied. 2+ The removal selectivity, such as Fig.15 As shown. CPI-BT in binary solution from 2+ Mg 2+ 、Ni 2+ , Sr 2+ and Zn 2+ (10~40mg / L) adsorption of UO2 in nuclear wastewater 2+ The experimental results show that CPI-BT has a good selectivity for UO2 2+ It has high selectivity and is 2+ Mg 2+ 、Ni 2+ and Sr 2+ ) in the presence of Zn. The adsorption capacity did not change much with the increase or decrease of the initial concentration of these competing ions. This indicates that the presence of other metal ions has no significant effect on the removal. However, in the presence of Zn 2+ In the presence of Zn, the adsorption capacity of CPI-BT decreased by about 30 mg / g, which was significantly lower than that of other cations, indicating that CPI-BT has a significant effect on Zn2+ The binding capacity of UO2 2+ Dominated the adsorption sites of CPI-BT.
[0095] Fig.16 A is the tannin-coupled cottonseed protein composite material prepared in Example 3 at different UO2 2+ Adsorption capacity at initial concentration. The results show that the adsorption capacity increases with the increase of concentration and reaches a maximum value of 310.15 mg / g at a concentration of 320 mg / L. 2+ concentration is not fully occupied, so the adsorbed UO2 2+ On the contrary, at high UO2 2+ At this concentration, the binding sites on CPI-BT are occupied and cannot bind more UO2 2+ When studying this process, it is crucial to understand the basic physicochemical behavior of the adsorption process as shown by the adsorption isotherm. 2+ The adsorption process can be described by the Freundlich and Langmuir isotherm models. These models explain some parameters related to the removal mechanism, including the surface characteristics of the adsorbent, its affinity for the adsorbate, and its removal capacity. Fig.16 BD and Table 2 show the fitting results. It is observed that CPI-BT has a significant effect on UO2 2+ The removal of is very consistent with the Langmuir isotherm model, and the regression coefficient is (R 2 >0.96). This indicates that the adsorption occurs on a homogeneous monolayer surface. According to the Langmuir model, CPI-BT for UO2 2+ The maximum removal capacity of CPI-BT was 224.72 mg / g. Therefore, CPI-BT can be used as a productive adsorbent.
[0096] Table 2
[0097]
[0098] After the uranium removal test, the resulting solution was collected and vacuum filtered using a 0.22 μm membrane, and the filtrate was then dried and used for subsequent characterization analysis. Fig.17 A is UO2 2+ SEM image and elemental composition of CPI-BT-U after adsorption. It can be seen that the adsorption of UO2 2+ After that, the surface of CPI-BT-U has the following characteristics: more pores, increased roughness, and finer particle shape; CPI-BT is mainly composed of C, O, and N atoms, however, a new peak appears in CPI-BT-U, indicating that UO2 2+ It has been successfully adsorbed onto the composite material. Fig.17 The EDS mapping image shown in C shows that UO2 2+ is highly dispersed throughout the material, indicating that a large fraction of UO2 2+ has been adsorbed on the active sites of CPI-BT, which also confirms that UO2 2+ is on the CPI-BT surface, as proposed by the Langmuir model above.
[0099] FTIR was used to study the changes in functional groups on CPI-BT after uranium removal experiments. Fig.17 As shown in B, after adsorption, the intensities of multiple peaks increased or decreased, and a new peak appeared. -1 A new peak appears at , which can be attributed to the stretching vibration of O=U=O, which proves that UO2 2+ Successfully chelated with CPI-BT. 3430cm -1 The peak at 1224 cm-1 is broadened, which is attributed to the strong stretching vibrations of -OH and -NH. -1 The peak at (typical phenolic hydroxyl peak) is significantly weakened, which indicates that UO2 2+ The substances removed include phenolic hydroxyl groups. The amide I, II and III bands of proteins are located at 1652 cm -1 、1535cm -1 and 1365cm -1 In addition, -C=O and -NH groups promote the UO2 2+ This is evidenced by the weaker peak intensities of the amide I, II, and III bands of CPI-BT-U.
[0100] To further understand the valence state of U adsorbed on CPI-BT, the XPS spectra of N1s and O1s were analyzed. Fig.18 A shows the XPS spectra of CPI-BT before and after the uranium removal test, UO2 2+ The treatment resulted in a new signal peak in the XPS full spectrum, which was U4f, indicating that UO2 2+ It was successfully adsorbed onto CPI-BT, which was consistent with the results of FTIR and EDS analysis. Fig.18 B is the high-resolution spectrum of U4f, in which five peaks are identified. The peaks at 380.40eV and 391.25eV are attributed to U(IV), and the peaks at 382.09eV, 385.57eV, and 392.90eV are attributed to U(VI). The functional groups contained in the protein or polyphenols in the composite material can act as electron donors, promoting the reduction of U(VI) to U(IV) during the adsorption process.
[0101] In the N1s XPS high-resolution spectrum ( Fig.18C), three peaks similar to those of natural CPI-BT were observed. However, the peaks at 400.68 eV, 399.38 eV, and 397.98 eV in CPI-BT were shifted. After the experiment, the peak of CN shifted to 399.28 eV. This shift may be due to the change in the electron density around the N atom when interacting with uranium. Due to the attraction of the positive metal ions to the outer electrons, the electron density of N is reduced, resulting in higher bonding energy. In the O1s XPS high-resolution spectrum ( Fig.18 In D), the two overlapping peaks at 532.28 eV and 530.98 eV correspond to C=O and COR, respectively. 2+ After adsorption, the peak position corresponding to COR shifted from 531.08 eV, which may be because the outer electrons of O atoms were attracted by the positively charged metal ions, increasing their bonding energy. The results also showed that the carboxyl groups on CPI participated in the adsorption process. In fact, through covalent bonds, both -NH and -C=O groups can contribute lone electron pairs and bind to UO2 2+ Chelation, CPI-BT for UO2 2+ The adsorption is mainly due to UO2 2+ The chelation process between the phenolic hydroxyl groups of BT combined with CPI. In addition, the -C=O and -NH of CPI are 2+ Active site for chelation.
[0102] Uranium purification performance test of fabric materials: a piece of cotton fabric with an area of 5cm×5cm was cut out uniformly; before the fabric material was contaminated with simulated uranium, its natural background value A0 was measured using an α, β surface contamination meter (RJ39-2060, Shanghai Ergonomics Testing Instrument Co., Ltd., Shanghai, China); it was uniformly soaked in 1mL 4.75g / L uranium solution for contamination, and then dried at 40℃; after the fabric was completely dried, the radioactivity value A1 was measured. The dried fabric was stirred at 180rpm in water / CPI-BT solution of different concentrations for 30 minutes, and then the fabric was taken out and dried at 40℃. After it was completely dried, its radioactivity value A2 was measured. The decontamination rate (DR) was calculated as follows:
[0103]
[0104] Surface uranium removal test of glass, metal and ceramic plates: New experimental plates of different materials (glass, metal and ceramic) with an area of 10 cm × 10 cm were cleaned with deionized water and dried until the surface was completely dry; before the simulated contamination, a square of 5 cm × 5 cm was drawn in the center of each plate, and the natural background value A0 of each plate was measured using an α, β surface contamination meter (RJ39-2060, Shanghai Ergonomics Testing Instrument Co., Ltd., Shanghai, China); then 4 mL of 4.75 g / L uranium solution was poured into the square drawn on the plate for contamination, and then dried in an oven at 45 ° C; after the plate was completely dried, the radioactivity value A1 was measured; a CPI-BT solution with a concentration of 0.2 mg / mL was prepared, and then the prepared CPI-BT decontaminant and water were sprayed on the contaminated surface, left to stand for 30 minutes, the solution was recovered, the plate was taken out, and dried in an oven at 45 ° C. After the plate was completely dried, its radioactivity value A2 was measured. The decontamination rate (DR) was calculated as follows:
[0105]
[0106] In order to expand the application range of CPI-BT, UO2 2+ The removal effect was tested. The contaminated cotton fabric material was washed with water and CPI-BT solution, and the UO2 2+ The amount removed was used to calculate the removal rate of CPI-BT on cotton fabric materials, such as Fig.19 As shown in A. The results showed that CPI-BT showed good removal efficiency for both α-U and β-U. When the dosage of CPI-BT was 20 mg, the removal rates of α-U and β-U were 88.4% and 73.0%, respectively. As the amount of CPI-BT increased from 20 mg to 100 mg, α-DR and β-DR increased significantly. In different dosages of CPI-BT and the control, α-DR was relatively higher than β-DR.
[0107] CPI-BT solution was used to decontaminate simulated radionuclides on ceramic, glass and metal surfaces. Fig.19 As shown in BD. Due to the sufficient number of active chelating sites on CPI-BT, complexation with active functional groups, adsorption and redox reactions facilitate the decontamination process. For all surfaces, the α-DR and β-DR values were significantly higher and >90%; compared with water alone, the DR of ceramic, glass and metal surfaces increased by 35.30%, 34.55% and 11.16%, respectively; compared with water alone, CPI-BT can effectively remove UO2 from different surfaces in a shorter time. 2+. Using wipes soaked in CPI-BT solution increased the α-DR and β-DR values for all surfaces by >95%, but this increase was minimal compared to using CPI-BT solution alone. Since radioactive contaminants are primarily physically bound to the surfaces of these materials, the contaminants are easily dissolved in the CPI-BT solution decontaminant, making it easy to eliminate the simulated radionuclides. In addition, previous studies have shown that the wettability of the sample to the surface significantly improves its decontamination efficiency, as higher wettability means a greater chance of contact between the sample and the radionuclide. This further proves that CPI-BT is a viable option for decontamination of radioactively contaminated surfaces.
[0108] Example 4
[0109] In this embodiment, the tannin-coupled cottonseed protein composite material obtained in Example 3 is modified, including:
[0110] Step 1: Take 1 g of the tannin-coupled cottonseed protein composite material prepared in Example 3 and add it to 200 mL of 70 wt% ethanol solution, then add 0.1 g of ferrous chloride and 0.1 g of polyethylene glycol-400, adjust the pH to 3, and stir at 25 ° C and 180 rpm for 3 h to obtain a mixed solution A;
[0111] Step 2: Add 0.2 g of tetrabutyl titanate and 0.1 g of citric acid to the mixed solution A, adjust the pH to 4, and stir at 45° C. and 180 rpm for 3 h to obtain a mixed solution B;
[0112] Step 3: add 100 mL of 0.3 mol / L sodium borohydride solution to the mixed solution B, stir at 25° C. and 180 rpm for 2 h, collect the precipitate by centrifugation, wash it, and freeze-dry it at -80° C. for 48 h to obtain a modified tannin-coupled cottonseed protein composite material.
[0113] In this embodiment, zero-valent iron and titanium oxide having adsorption and reduction activity for uranyl ions are introduced to further modify the obtained tannin-coupled cottonseed protein composite material, and polyethylene glycol-400 and citric acid are used as reaction aids to avoid agglomeration of various substances, improve dispersibility, and make the reaction more uniform and sufficient. The uranium removal ability of the modified tannin-coupled cottonseed protein composite material is further enhanced.
[0114] Example 5
[0115] In this embodiment, the tannin-coupled cottonseed protein composite material obtained in Example 3 is modified, including:
[0116] Step 1: Take 1 g of the tannin-coupled cottonseed protein composite material prepared in Example 3 and add it to 200 mL of 70 wt% ethanol solution, then add 0.1 g of ferrous chloride and 0.1 g of polyethylene glycol-400, adjust the pH to 3, and stir at 25 ° C and 180 rpm for 3 h to obtain a mixed solution;
[0117] Step 2: add 100 mL of 0.3 mol / L sodium borohydride solution to the mixed solution, stir at 25° C. and 180 rpm for 2 h, collect the precipitate by centrifugation, wash it, and freeze-dry it at -80° C. for 48 h to obtain a modified tannin-coupled cottonseed protein composite material.
[0118] Example 6
[0119] In this embodiment, the tannin-coupled cottonseed protein composite material obtained in Example 3 is modified, including:
[0120] Step 1: Take 1 g of the tannin-coupled cottonseed protein composite material prepared in Example 3, add it to 200 mL of 70 wt% ethanol solution, then add 0.2 g of tetrabutyl titanate and 0.1 g of citric acid, adjust the pH to 4, and stir at 45 ° C and 180 rpm for 3 h to obtain a mixed solution;
[0121] Step 2: add 100 mL of 0.3 mol / L sodium borohydride solution to the mixed solution, stir at 25° C. and 180 rpm for 2 h, collect the precipitate by centrifugation, wash it, and freeze-dry it at -80° C. for 48 h to obtain a modified tannin-coupled cottonseed protein composite material.
[0122] The tannin-coupled cottonseed protein composite materials prepared in Examples 4 to 6 were subjected to a uranium removal test in a water environment, and the uranium removal rates RE were shown in Table 3. It can be seen that the tannin-coupled cottonseed protein composite materials are further modified in the present invention, and the uranium removal capacity of the modified tannin-coupled cottonseed protein composite materials is further enhanced, with a uranium removal rate of >95%, of which Example 4 has the highest of 98.0%.
[0123] The tannin-coupled cottonseed protein composite materials prepared in Examples 4 to 6 were subjected to a test of uranium purification performance on fabric materials, and the decontamination rates DR were shown in Table 4. It can be seen that the tannin-coupled cottonseed protein composite materials prepared in Examples 4 to 6 have better decontamination rates for α-U and β-U on cotton fabric materials than those in Example 3.
[0124] Table 3
[0125] Example 3 Example 4 Example 5 Example 6 Uranium removal rate RE (%) 93.8 98.0 96.5 97.2
[0126] Table 4
[0127] Example 3 Example 4 Example 5 Example 6 Decontamination rate DR (α-U) (%) 88.4 93.3 90.2 91.5 Decontamination rate DR (β-U) (%) 73.0 79.1 75.8 77.9
[0128] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A tannin-coupled cottonseed protein composite material for uranium removal, characterized in that: The tannin-coupled cottonseed protein composite material is used for uranium removal in water environment.
2. A method for preparing a tannin-coupled cottonseed protein composite material for uranium removal as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Add cottonseed protein to distilled water under a nitrogen atmosphere, stir, then add hydrogen peroxide solution and ascorbic acid, continue stirring to obtain a cottonseed protein mixed solution; Step 2: adding plant tannin to the cottonseed protein mixture to make the concentration of the plant tannin in the mixture be 0.3-1.1 mmol / L, stirring for reaction, dialyzing to remove unreacted plant tannin, and freeze-drying to obtain a tannin-coupled cottonseed protein composite material for uranium removal.
3. The method for preparing a tannin-coupled cottonseed protein composite material for uranium removal according to claim 2, characterized in that: In the step 1, the mass volume ratio of cottonseed protein to distilled water is 1 g:50-150 mL.
4. The method for preparing a tannin-coupled cottonseed protein composite material for uranium removal according to claim 2, characterized in that: In the step 1, the stirring temperature is 20 to 30° C., and the stirring time is 1 to 3 hours.
5. The method for preparing a tannin-coupled cottonseed protein composite material for uranium removal according to claim 2, characterized in that: In the step 1, the concentration of the hydrogen peroxide solution is 0.5 to 1.5 mol / L.
6. The method for preparing a tannin-coupled cottonseed protein composite material for uranium removal according to claim 2, characterized in that: In the step 1, the mass volume ratio of cottonseed protein to hydrogen peroxide solution is 1 g: 1-5 mL; the mass volume ratio of cottonseed protein to ascorbic acid is 1: 0.2-0.
7.
7. The method for preparing a tannin-coupled cottonseed protein composite material for uranium removal according to claim 2, characterized in that: In the step 2, the plant tannin is one or more of bayberry tannin, persimmon tannin, apple tannin, tea tannin and grape tannin.
8. The method for preparing a tannin-coupled cottonseed protein composite material for uranium removal according to claim 2, characterized in that: In the step 2, the stirring reaction temperature is 20 to 30° C. and the time is 20 to 30 hours; the freeze drying is freeze drying at -100 to -50° C. for 40 to 60 hours.
9. Use of the tannin-coupled cottonseed protein composite material for uranium removal prepared by the preparation method according to any one of claims 2 to 8 in removing uranium from textile materials.
10. Use of the tannin-coupled cottonseed protein composite material for uranium removal prepared by the preparation method according to any one of claims 2 to 8 in the removal of uranium from glass, metal and ceramic surfaces.
Citation Information
Patent Citations
Nano gelatin / polymer composite fiber belt preparation method based on seawater uranium extraction
CN108745320A
Cottonseed protein intermediate as well as preparation method and application thereof
CN115772332A
Method for preparing sulfonated emulsifier based on cottonseed protein isolate
CN116925784A
Protein-polyphenol composite nanoparticle, preparation method and application of protein-polyphenol composite nanoparticle in antioxidant Pickering emulsion
CN118633675A
Biosorbents for removal of contaminants from waste / oil sand process-affected water (OSPW) and consolidation of oil sands tailings
US20170210641A1